Geochronology and geochemistry of late Cenozoic volcanics on Naozhou Island, South China: insights into the interaction between the paleo-subduction slab and the Hainan mantle plume - Xu, Jin; Xie, Hui; Luo, Zixuan; Chen, Yanting; Shi, Hongcai (Frontiers in Earth Science, 2025)
The mechanisms and processes of interaction between paleo-subducted slabs and mantle plumes are not well understood, primarily due to the challenges associated with direct observation. The Leiqiong Area (LQA), located in the northwestern South China Sea (SCS), may provide an ideal site to study the interaction between mantle plumes and paleo-subducted slabs. Extensive Late Cenozoic volcanic activities are present in the LQA, encompassing the Leizhou Peninsula (LP) and northern Hainan Island. This study conducted K-Ar dating, major and trace element analysis, and Sr-Nd-Pb-Hf isotopic analysis on volcanic rock samples from Naozhou Island, the largest volcanic island in the northeastern part of the LQA. The dating results show two periods of magmatic activities on Naozhou Island (3.6 Ma and 1 Ma). The geochemical results indicate that the columnar jointed basalts from Naozhou Island mainly show characters of oceanic island basalt (OIB). The isotopic data suggest origins of depleted MORB mantle (DMM) and Enriched Mantle Ⅱ (EMⅡ), with EMⅡ potentially originating from the Hainan mantle plume. In view of these findings, the study further integrates data (Geochronology, trace elements and isotopic composition) from other volcanic rocks in the LQA to explore the deep mechanisms of extensive volcanic activity and plume-slab interactions along the northwestern SCS margin. We discovered that the volcanic rocks from southern LP and northern Hainan Island are characterized by OIB, IAB and OIB-IAB transition like, however, the volcanic rocks from Naozhou Island (northern LP) and Weizhou Island (western LP) are characterized by OIB like merely. This can be explained by a branched Hainan mantle plume model and may indicate the interaction between Hainan mantle plume and paleo-subdected slab mainly focuse on the center location of the plume rather than distal margin. This conjecture is also in accord with the subduction direction of the Late Mesozoic subduction zone along the northern margin of the SCS.